Evaluasi Pengaruh Penggunaan Jenis Material Dan Ukuran Kedalaman Stemming Dalam Kegiatan Peledakan Terhadap Hasil Fragmentasi, Cost, Dan Recovery Blasting Di PT. Koto Alam Sejahtera Kabupaten Lima Puluh Kota Provinsi Sumatera Barat - Fitrya Monica; Dedi Yulhendra (Journals Mining Engineering : Bina Tambang, 2021)
.  At PT. Koto Alam Sejahtera still found fragmentation of boulder ≥ 50 cm, when using drill cutting, it was found that the boulder was 32.1% on average, so it did not match the target ≤15%. When using 1-2 cm of split stone stemming material, it produces an average boulder ≥ 50 cm of 3,1 %. The use of 1-2 cm split stone stemming material results in a fragmentation size, better recovery compared to the result of using drill cutting stemming material, but the use of 1-2 cm split stone stemming material requires additional costs for the purchase of stemming material and in each stemming depth measurement. used to produce different fragmentation sizes. The blasting recovery target was not achieved in July, which was only 72.4% from 90%. The purpose of this study was to determine the effect of stemming depth and use of stemming material on stemming performance on the results of the distribution of fragmentation, costs and blasting recovery. The research method was carried out using stemming depth measuring 1.6 m, 1.7 m, and 1.8 m which will be tested using 2 types of stemming material, namely cutting drill and 1-2 cm split rock material. To recommend the selection with R.L Ash theory, 4 proposed depth measurements were obtained, so that the appropriate stemming depth measurement was 1.6 m. And the use of stemming material is based on actual blasting results using drill cuttings and 1-2 cm split stones. Because the result of 1-2 cm split stone blasting is better but requires additional costs for the purchase of stemming material, the mixing of the two materials is done to reduce the purchase cost, so a 65% split stone mixture is used and drill cutting 35%. The results of the recommendations using the stemming depth measure and the use of stemming mixture materials resulted in more optimal blasting with an average boulder percent of the two triyal activities analyzed using a split desktop resulting in a boulder> 50 cm of 0%. The average recovery value obtained was 90.7% and reduced blasting operation costs to $ 12.956114 / hole.